2013
DOI: 10.7498/aps.62.129201
|View full text |Cite
|
Sign up to set email alerts
|

A study on precipitation trend and fluctuation mechanism in northwestern China over the past 60 years

Abstract: This paper focuses on the mechanism of the trend and oscillation in precipitation records in northwestern China over the past 60 years. The results from regression and orthogonal wavelet decomposition show a clearly ascending in annual precipitation since 2000, which is contributed mostly by significant increase in autumn and winter precipitations, while almost no trend can be identified in spring and summer time, which shows a weak descending in non-linear form. This may be in connection with different warmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The sources of water vapor in spring, autumn and winter in Central Asia include the Arctic Ocean, the Mediterranean Sea, the Black Sea and the Caspian Sea, whereas the water vapor in summer mainly comes from the Atlantic Ocean and continental Europe in the mid-and high latitudes (Shi and Sun, 2008;Guan et al, 2019). Dai et al (2011) analyzed the constant water vapor field in the troposphere from Xinjiang to the Atlantic Ocean and found that the main sources of water vapor in Xinjiang were from lakes and oceans to the west. With the current trend in global warming, more water vapor is sourced from high latitudes, such as the North Atlantic and Arctic oceans.…”
Section: Introductionmentioning
confidence: 99%
“…The sources of water vapor in spring, autumn and winter in Central Asia include the Arctic Ocean, the Mediterranean Sea, the Black Sea and the Caspian Sea, whereas the water vapor in summer mainly comes from the Atlantic Ocean and continental Europe in the mid-and high latitudes (Shi and Sun, 2008;Guan et al, 2019). Dai et al (2011) analyzed the constant water vapor field in the troposphere from Xinjiang to the Atlantic Ocean and found that the main sources of water vapor in Xinjiang were from lakes and oceans to the west. With the current trend in global warming, more water vapor is sourced from high latitudes, such as the North Atlantic and Arctic oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Since the end of 1980s, the climate in Xinjiang Uygur autonomous region has been warming and humidifying as a result of global climate change [8]. In the past 20 years since the beginning of the 21st century, there have been two trends in Xinjiang Uygur autonomous region's climate: one is that the total precipitation in Xinjiang Uygur autonomous region continues to increase; the other is that extreme precipitation events have fluctuated and increased [9], significantly affecting the vegetation in the desert areas [10]. Therefore, the study of morphological and photosynthetic characteristics of Haloxylon ammodendron under water and salt gradient will provide scientific basis for the response of Haloxylon ammodendron to global change.…”
Section: Introductionmentioning
confidence: 99%